Improving The Marketing Performance of Tasikmalaya Weaving Industry Through Product Innovation - Muhammad Shidqi Akhmal Pratama; Lusi Suwandari (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of digital literacy on the marketing performance of woven industry MSMEs in Tasikmalaya, with product innovation as a mediating variable. The quantitative approach was used through a survey of 121 MSME actors in the Tasikmalaya weaving industry. Data analysis was carried out using the Structural Equation Modeling (SEM) method using  SmartPLS 4 software. The results of the study show that digital literacy has a significant effect on product innovation and marketing performance. In addition, product innovation has been shown to mediate the relationship between digital literacy and marketing performance. These findings affirm the importance of mastery of technology and innovative capabilities for MSME actors to increase competitiveness and marketing effectiveness. This research makes a practical contribution to the development of digital-based MSME empowerment strategies.